Pengaruh Kinerja Keuangan dan Pengungkapan Sustainability Report terhadap Harga Saham: Pada Perusahaan Sub-Industri Hotel, Resort, dan Cruise Lines yang Terdaftar di Bursa Efek Indonesia Periode 2019-2024 - Vana Jelita; Antonius Bimo Rentor Luntungan; Putri Gantine Lestari (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
The capital market is a place for various investment instruments, ranging from short-term to long-term. Before buying shares in the capital market, investors need to analyze the share prices of selected companies to predict large profits. The higher the share price, the greater the possibility of making a profit. This study aims to determine the factors that influence the stock prices of companies in the hotel, resort, and shipping sub-sectors listed on the IDX for the period 2019–2024. The dependent variable in this study is stock price, while the independent variables are financial performance and sustainability report disclosure. Financial performance variables are proxied by DER, Current Ratio, ROA, and TATO. This is a quantitative study using secondary data obtained from annual reports and sustainability reports taken from the companies' official websites. The number of samples used in this study is 10 companies using classical assumption techniques, multiple linear regression analysis, determination tests, and ending with hypothesis testing. The results show that DER and Current Ratio have a negative effect on stock prices. ROA, TATO, and sustainability report disclosure partially have no effect on stock prices. Meanwhile, financial performance and sustainability report disclosure simultaneously affect stock prices.